The torture camp on paradise street - Aseev, Stanislav, 1989-; Tompkins, Zenia; Shevchuk-Murray, Nina (Cambridge, Massachusetts : Ukrainian Research Institute, Harvard University, 2023)
In the memoir The Torture Camp on Paradise Street, Ukrainian journalist and writer Stanislav Aseyev details his experience as a prisoner for nearly three years at a modern-day concentration camp overseen by the Federal Security Bureau of the Russian Federation (FSB) in the Russian-controlled city of Donetsk.
The arrival -- Isolation and the prison code -- Fear -- Pure evil -- The hour of the quiet ones -- Madness or normalcy? -- Time in captivity -- The blue light: To kill yourself or not? -- Torture: A personal experience -- What broke me -- Sex in isolation -- The escape -- A hunger strike is not a way out -- Why there was never an uprising -- Mouseville: Writing in spite of -- God behind bars -- Humor in captivity -- Who are these people? -- A strange survey -- The man with the dog -- An exercise in death and freedom -- Not in Prague -- White nights -- Christ in a Gulag -- Named after Vladimir Lenin -- Something about someone -- Heroes of the tocsin -- To a future me -- The bell -- Of pipes and men -- An essay about a volcano -- An atheist's prayer.
Print version record.
JSTOR
Keywords: Aseev, Stanislav, -- 1989- -- Imprisonment; Sluzhba vneshneĭ razvedki Rossiĭskoĭ Federat͡sii; Sluzhba vneshneĭ razvedki Rossiĭskoĭ Federat͡sii; Internment camps -- Ukraine -- Donet͡sʹk.; Political prisoners -- Ukraine -- Donet͡sʹk.; Russo-Ukrainian War, 2014- -- Prisoners and prisons -- Biography; Prisoners of war -- Ukraine -- Donet͡sʹk -- Biography; Journalists -- Ukraine -- Biography; Russo-Ukrainian War, 2014- -- Concentration camps -- Ukraine -- Donet͡sʹk.; Russo-Ukrainian War, 2014- -- Atrocities -- Ukraine -- Donet͡sʹk.; Camps d'internement -- Ukraine -- Donetsk; Prisonniers politiques -- Ukraine -- Donetsk; Prisonniers de guerre -- Ukraine -- Donetsk -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; Imprisonment; Internment camps; Political prisoners; Ukraine -- Donet͡sʹk; Electronic books; Personal narratives; Biographies; Récits personnels; Biographies